PERBANDINGAN PENGARAUH TEKNIK READING QUIZ DENGAN QUESTION STUDENT HAVE TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPS DI SMPN 1 PALEMBANG - Ayu Deta Lestari; Siti Fatimah; Rusmin AR (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2016)
The purpose of this research to prove the difference influence between technique Reading Quiz with Question Student Have tolearning’s outcomes of students in social studies lesson at SMPN 1 Palembang. This research uses the quantitative method. The research population was the whole class VIII SMPN 1 Palembang second semester of the 2015/2016 academic year. The research sample using cluster sampling.Data collection techniques in the form of tests and observation. The result from analysis there are differences of impact that technique Reading Quiz higher than technique Question Student Have to learning’s outcomes of students in learning social studies at SMPN 1 Palembang. The results of the analysis of experimental observations on the class-1 can be interpreted in learning activities direct from learning is very strong and the other one on eksperimen-2 is strong. Advice relating to the use of techniques Reading Quiz can foster self-confidence for student to face learners and Reading Quiz. While the technique of Question Student Have if the classroom allows the better position of learners should be circular.